Chemoradiation versus local excision in treatment of stage I anal squamous cell carcinoma: A population-based analysis. Issue 9 (September 2020) - Gao, Xiang; Goffredo, Paolo; Kahl, Amanda R.; Charlton, Mary E.; Weigel, Ronald J.; Hassan, Imran
Abstract: Introduction: Chemoradiation therapy (CRT) is the standard treatment for anal squamous cell carcinoma (ASCC) but can have significant treatment related toxicities. Recent studies have demonstrated the effectiveness of local excision (LE) for stage I ASCC with comparable oncologic outcomes to CRT. We aimed to evaluate this finding in a large population-based database. Methods: Patients diagnosed with stage I (T1N0M0) ASCC were identified from the Surveillance, Epidemiology, and End Results database, 2004–2015. Treatment approach was categorized as CRT or LE. Factors associated with treatment approach and cause-specific survival (CSS) were analyzed for the entire cohort and after stratification by tumor size (≤1 cm and 1–2 cm). Results: Among 883 patients, 56% had ASCCs 1–2 cm in size and 77% received CRT. Mean age was 60 years, 65% were female, and 90% were White. Factors independently associated with receiving CRT were, being female, higher tumor grade, and tumor size 1–2 cm. Unadjusted 5-year CSS for CRT was 96% while for LE it was 98% (p = 0.048). After adjusting for available confounders, treatment approach was not associated with worse CSS, however being Black (HR = 8.7) and uninsured (HR = 13.7) were independently associated with worse prognosis. After stratification by tumor size, there was still no significant difference in 5-year CSS by treatment approach. Conclusions: LE was performed in a significant proportion of patients but was not independently associated with worse CSS compared to CRT. In appropriately selected patients with well differentiated ASCCs ≤1 cm, LE could be an acceptable management option but studies measuring outcomes such as local recurrence are needed.